1975
DOI: 10.1152/jappl.1975.39.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of arterial hypoxemia following pulmonary thromboembolism in dogs

Abstract: Mongrel dogs (29) were anesthetized, paralyzed, and ventilated at a constant minute volume. AaD02 breathing air and 100% O2, venous admixture breathing air (Qva/Qt) and 100% O2 (Qs/Qt), single-breath diffusing capacity for CO (DLCO), and total pulmonary resistance (RL) and pulmonary compliance (CL) were measured before and after pulmonary embolization with autologus in vivo venous thrombi. Nine dogs were heparinized before embolization. In the 20 nonheparinized dogs AaDo2 breathing air increased from 11 to 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…result of decreased transit time of blood through a reduced pulmonary capillary bed with resulting failure of alveolar-end capillary equilibration (18). Recently, VA/Q inequality and intrapulmonary shunt have been implicated as causes for the hypoxemia (19)(20)(21). A low cardiac output state with resulting reduction of mixed venous saturation has also been reported (22), but its impact on arterial hypoxemia has not been evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…result of decreased transit time of blood through a reduced pulmonary capillary bed with resulting failure of alveolar-end capillary equilibration (18). Recently, VA/Q inequality and intrapulmonary shunt have been implicated as causes for the hypoxemia (19)(20)(21). A low cardiac output state with resulting reduction of mixed venous saturation has also been reported (22), but its impact on arterial hypoxemia has not been evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxemia and impaired gas exchange indices calculated as a function of inspired oxygen concentration include PaO2/FiO2, a/APO2 and AaDO2. 5,13,14 In the present study, ROC curve analysis found that PaO2/FiO2 was inferior to both the a/APO2 and AaDO2 for comparing gas exchange under room air. If FiO2 was more than 0.21, the area under the ROC curve for PaO2/FiO2 was slightly smaller than that for a/APO2 (0.709 vs 0.714).…”
Section: Mechanisms Of Impaired Gas Exchange and Index Of Gas Exchangmentioning
confidence: 41%
“…9 Other proposed mechanisms have been reported and revealed minor roles. [10][11][12][13] Several parameters are derived from ABG analysis. Hypoxemia and impaired gas exchange indices calculated as a function of inspired oxygen concentration include PaO2/FiO2, a/APO2 and AaDO2.…”
Section: Mechanisms Of Impaired Gas Exchange and Index Of Gas Exchangmentioning
confidence: 99%
“…Air shift from the embolized lung areas has been demonstrated in animal models [15,16]. In humans this component is not demonstrated.…”
Section: Discussionmentioning
confidence: 99%